2005
DOI: 10.5713/ajas.2006.80
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Essential Oils Supplementation on Growth Performance, IgG Concentration and Fecal Noxious Gas Concentration of Weaned Pigs

Abstract: Ninety six crossbred pigs (Landrace×Yorkshire×Duroc) were used to determine the effects of essential oils (Fresta F Conc ® ) supplementation on growth performance, immune response and fecal noxious gas of weaned pigs. Treatments were 1) NC (negative control; basal diet without antibiotics), 2) PC [positive control; basal diet+CSP (CTC+Sulfathiazole+Penicillin) 0.1%], 3) NCF (basal diet+Fresta F Conc ® 0.03%) and 4) PCF [basal diet+CSP (CTC+Sulfathiazole+Penicillin) 0.1%+Fresta F Conc ® 0.02%]. From d 0 to 14, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
82
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(103 citation statements)
references
References 7 publications
(10 reference statements)
19
82
0
2
Order By: Relevance
“…In the current study, the apparent digestibility of N was improved by 0.5% BA supplementation on d 21, which was in agreement with the results reported by Halas et al (2010). Meanwhile, the ATTD of DM and N was improved in the dietary treatment combined application of 0.3% BA and 0.01% EO, which was consistent with the results of Cho et al (2006), who reported that 0.02% EO could improve the digestibility of DM and N in weaned pigs. Yan et al (2012) also demonstrated that herb extract could stimulate the nutrient digestibility and suggested that the beneficial effects may arise from the activation of digestive enzyme secretion, antibacterial and antioxidant properties (Czech et al 2009).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In the current study, the apparent digestibility of N was improved by 0.5% BA supplementation on d 21, which was in agreement with the results reported by Halas et al (2010). Meanwhile, the ATTD of DM and N was improved in the dietary treatment combined application of 0.3% BA and 0.01% EO, which was consistent with the results of Cho et al (2006), who reported that 0.02% EO could improve the digestibility of DM and N in weaned pigs. Yan et al (2012) also demonstrated that herb extract could stimulate the nutrient digestibility and suggested that the beneficial effects may arise from the activation of digestive enzyme secretion, antibacterial and antioxidant properties (Czech et al 2009).…”
Section: Discussionsupporting
confidence: 82%
“…It has been demonstrated that 0.01-0.05% EO exert positive effects on the nutrient digestibility, growth performance, decrease faecal noxious gas emission and have antimicrobial effects in piglets (Cho et al 2006;Yan et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research (Didry et al, 1994;Tsinas et al, 1998) found that essential oils enhanced the regulation of gastrointestinal metabolism and exerted antibacterial properties in the digestive tract of pigs. Cho et al (2006) demonstrated that NH 3 concentration in faeces was signifi cantly reduced by addition of essential oils by improving N digestibility. However, in our study, no improvements in N digestibility were noted when sows were fed on diets supplemented with PFA.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the studies suggested that supplementation of plant extracts and essential oil blends does not improve performance of weaning pigs, regardless of whether carvacrol or thymol is contained or not (Namkung et al, 2004;Cho et al, 2006;Kommera et al, 2006;Manzanilla et al, 2006;Nofrarias et al, 2006). For example, the dietary supplementation with the plant extract containing 5% (w/w) carvacrol, 3% cinnamaldehyde and 2% capsicum oleoresin at dose of 300 mg/kg does not affect the performance of weaning pigs Nofrarias et al, 2006).…”
Section: Figure 1 Population Of Enterococcus Genus (A) Escherichia Cmentioning
confidence: 99%